2010
DOI: 10.1021/bm100922j
|View full text |Cite
|
Sign up to set email alerts
|

Highly Branched Polymers with Polymyxin End Groups Responsive to Pseudomonas aeruginosa

Abstract: Polymyxin peptide conjugated to the end groups of highly branched poly(N-isopropyl acrylamide) was shown to bind to a Gram negative bacterium, Pseudomonas aeruginosa . The nonbound polymer had a lower critical solution temperature (LCST) above 60 °C. However, binding caused aggregation, which was disrupted on cooling of the bacteria and polymer mixture. The data indicate that polymer binding of bacteria occurred by interaction of the end groups with lipopolysaccharide and that the binding decreased the LCST to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…This shows that these polymers, which have been shown to be stimuli-responsive to bacteria in solution and to be useful for aggregation of bacteria [23], [37], [38], had broad molar mass distributions and that molar mass distributions changed following modification and purification (ultra-filtration and precipitation).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…This shows that these polymers, which have been shown to be stimuli-responsive to bacteria in solution and to be useful for aggregation of bacteria [23], [37], [38], had broad molar mass distributions and that molar mass distributions changed following modification and purification (ultra-filtration and precipitation).…”
Section: Resultsmentioning
confidence: 92%
“…However, chain end functionalization affects their solubility in traditional SEC solvents [23], [37], [38]. The advent of a methanol based system means for the first time it will be possible to disclose the molar mass of these materials before and after chain-end modification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results have important implications for the production of stimulus responsive devices because they indicated that the end groups: 1) penetrate to a limited degree into the polymer coil and 2) that only small changes in the solvation of end groups (e.g. 5 binding to receptors) would be required to drive these materials through a phase transition because the solvation of the shell would be dominated by the penetration of the end groups. Penetration of polar end groups (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…70,71 pH is an attractive stimulus given the range found throughout the body and in diseased tissues. 70,71 pH is an attractive stimulus given the range found throughout the body and in diseased tissues.…”
Section: (Ii) Triggering An "Isothermal" Response Via End-group Modifmentioning
confidence: 99%